ChemInform Abstract: Flow Synthesis of Ethyl Isocyanoacetate Enabling the Telescoped Synthesis of 1, 2, 4‐Triazoles and Pyrrolo‐[1, 2‐c]pyrimidines. Issue 32 (August 2015) - Baumann, Marcus; Rodriguez Garcia, Antonio M.; Baxendale, Ian R.
Abstract The dehydration of N‐formylglycine (I) with triphosgene in a continuous flow reactor leads to a stream of ethyl isocyanoacetate, which reacts with in situ generated diazonium salts to afford desired 1, 2, 4‐triazoles.